The Polish EU presidency in the Polish press: Did we actually notice it? - Stępińska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The aim of this paper is to present the findings of a quantitative content analysis of the Polish print media. Sharing the codebook and procedures with an international team, we were able to gain a broad perspective on the media coverage of the first Polish EU presidency. In particular, we focused on: (1) the number of items covering events related to the presidency, (2) the prominence of the topic, (3) genres, (4) main topics, (5) authors of news, (6) authors of opinions, and (7) the way Polish journalists evaluated Poland’s performance during the EU presidency. The findings showed that although Polish print press reported the first Polish EU presidency, the topic’s prominence was not very high. Media organizations rather rarely presented the topic on the front page and they did not change their regular editorial policy. Most of the news items, as well as opinions and comments, were written by staff members. Furthermore, journalists seemed to be more interested in the opinions of national politicians, rather than experts. As a result, the framework of the coverage was predominantly domestic. Journalists working for daily newspapers focused mostly on providing news and their own interpretations of the reported events. On the contrary, weekly magazines provided comments and interviews, but again, most of the opinions were expressed by their own journalists and editors.